LARGEST SPECIMEN OF BIG-JAWED JUMPER, LACTARIUS LACTARIUS (SCHNEIDER) - Shanmugavelu, C R (Indian Journal of Fisheries, 2011)
A specimen of Lactarius lactarius 330 mm total length was recorded from a drift net catch at Pamban (Gulf of Mannar). The largest specimen of this species recorded so far had only 23 rays in the anal fin as against 72-28 rays in the normal specimens.